Beam dynamics simulation with the use of macroparticle «PROTON» code in different variants of input dynamical matchers in a heavy ion high current RFQ structure - Vorobyov, I.A. (Вопросы атомной науки и техники, 2006)
Beam dynamics simulations with the use of macroparticle method were performed for two cases of input dynamical
matchers for RFQ. It is done a comparison with data obtained from the envelope equations. These simulation results
are in agreement with other simulation and theoretical ones. Численное исследование динамики пучка методом крупных частиц выполнено в двух вариантах входного динамического согласователя для ПОКФ. Сделано сравнение с данными, полученными по уравнениям для огибающих. Результаты численного моделирования находятся в соответствии с данными других расчётов. Чисельне дослідження динаміки пучка методом великіх часток виконано у двох варіантах вхідного
динамічного узгоджувача для ПОКФ. Зроблено порівняння з даними, отриманими по рівняннях для
обгинаючих. Результати чисельного моделювання відповідають даним інших розрахунків.